2021
DOI: 10.1038/s41375-021-01313-2
|View full text |Cite
|
Sign up to set email alerts
|

NK-/T-cell lymphomas

Abstract: Natural killer/T-cell lymphoma (NKTL) is a sub-type of Epstein–Barr virus (EBV)-related non-Hodgkin lymphomas common in Asia and Latin America but rare elsewhere. Its pathogenesis is complex and incompletely understood. Lymphoma cells are transformed from NK- or T-cells, sometimes both. EBV-infection and subsequent genetic alterations in infected cells are central to NKTL development. Hemophagocytic syndrome is a common complication. Accurate staging is important to predict outcomes but there is controversy wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 125 publications
3
69
0
Order By: Relevance
“…We will not discuss these in details, but excellent reviews, such as those from Nebrinsky and co-workers, Chung et al, Klener and Klanova, or Othman and co-workers are suggested in this topic for those interested [370,381,384,385]. In addition, therapeutic challenges for NK/T-cell lymphomas are discussed in articles, such as the ones from Xue and Zhang, or Wang and co-workers [386,387]. nHLs and mitochondria.…”
Section: Non-hodgkin Lymphomas (Nhls)mentioning
confidence: 99%
“…We will not discuss these in details, but excellent reviews, such as those from Nebrinsky and co-workers, Chung et al, Klener and Klanova, or Othman and co-workers are suggested in this topic for those interested [370,381,384,385]. In addition, therapeutic challenges for NK/T-cell lymphomas are discussed in articles, such as the ones from Xue and Zhang, or Wang and co-workers [386,387]. nHLs and mitochondria.…”
Section: Non-hodgkin Lymphomas (Nhls)mentioning
confidence: 99%
“…ENKTL is a tumor of either NK cell or cytotoxic T cell lineage. T and NK cells originate from the same lymphoid progenitor cells and develop into different cell lineages with the rearrangement of TCR gene [40]. Because T and NK cells share the expression of some T and NK cell markers, the cell lineage cannot be distinguished only by immunophenotype; instead, it is determined by either the TCR gene rearrangement or the expression of the TCR antigen.…”
Section: Cell Of Originmentioning
confidence: 99%
“…Extranodal NK/T-cell lymphoma (ENKTL) is a highly aggressive lymphoma that has a geographic predilection in Asian and South American populations (1)(2)(3)(4). In China, the incidence of ENKTL is higher and secondary to the diffuse large B-cell lymphoma, accounting for approximately 11% of all lymphomas (5).…”
Section: Introductionmentioning
confidence: 99%